2002
DOI: 10.1086/342582
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Febrile Gastroenteritis Associated with Delicatessen Meat Contaminated withListeria monocytogenes

Abstract: In June 2001, the Los Angeles County Department of Health Services/Public Health conducted a cohort study of an outbreak of acute febrile gastroenteritis among 16 of 44 healthy attendees of a catered party. The median age of the attendees who became ill was 15.5 years. Symptoms included body aches (in 88% of attendees), fever (81%), headache (81%), diarrhea (63%), and vomiting (56%). Illness was associated with ingestion of precooked, sliced turkey (P=.000004). Six stool specimens yielded Listeria monocytogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
51
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(54 citation statements)
references
References 28 publications
0
51
0
3
Order By: Relevance
“…monocytogenes accounted for the greatest number of food product recalls (9,31,39) and several recent outbreaks (10,11,23,31). Therefore, rapid and sensitive methods are required to detect this pathogen in food.…”
Section: Discussionmentioning
confidence: 99%
“…monocytogenes accounted for the greatest number of food product recalls (9,31,39) and several recent outbreaks (10,11,23,31). Therefore, rapid and sensitive methods are required to detect this pathogen in food.…”
Section: Discussionmentioning
confidence: 99%
“…For all others not exquisitely sensitive to listeriosis, exposure to L. monocytogenes is seldom fatal. Several outbreaks of L. monocytogenes-associated febrile gastroenteritis have been reported among healthy adults, but only at doses of 10 5 CFU or greater (1,4,8,17). Concern about listeriosis led the Center for Food Safety and Applied Nutrition of the U.S. Food and Drug Administration (FDA), the Food Safety Inspection Service of the U.S. Department of Agriculture (USDA), and the Centers for Disease Control and Prevention (CDC) to conduct a risk assessment for L. monocytogenes in ready-to-eat foods (7).…”
mentioning
confidence: 99%
“…Rarely, outbreaks have been caused by non-4b serotypes. For example, a serotype-3a strain outbreak was linked to contaminated butter in Finland (22), and a serotype-1/2a outbreak of gastrointestinal listeriosis was linked to sliced turkey in the United States (11). Previous studies have also shown that lineage I strains are more common among human listeriosis cases and outbreaks than among animal cases, while lineage III strains are significantly more common among animal listeriosis cases than among human cases (17).…”
mentioning
confidence: 99%